2008
DOI: 10.3758/pbr.15.5.889
|View full text |Cite
|
Sign up to set email alerts
|

Toward a complete decision model of item and source recognition

Abstract: In a recognition memory test, subjects may be asked to decide whether a test item is old or new (item recognition) or to decide among alternative sources from which it might have been drawn for study (source recognition). Confidence-rating-based receiver operating characteristic (ROC) curves for these superficially similar tasks are quite different, leading to the inference of correspondingly different decision processes. A complete account of source and item recognition will require a single model that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
122
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(132 citation statements)
references
References 36 publications
9
122
1
Order By: Relevance
“…If source discrimination relies primarily on the high-threshold recollection process, then the rec ognition zROCs should have a shallower slope for source-correct than source-incorrect items and the refined source zROC must be u-shaped (see Figure ,3, Panel 1). If familiarity drives source 3 The BBG model is similar, but not identical, to the proposal that participants make random source guesses for any item they fail to recog nize (Hautus et al, 2008;Slotnick & Dodson, 2005). One critical differ ence is that the point where the bounded distributions converge is not determined by a participant's criterion for making an "old" response, so in the BBG model, it is possible for "new" responses to have above chance source discrimination if the recognition criterion is sufficiently conserva tive (as observed by Stams, Hicks, Brown, & Martin, 2008).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…If source discrimination relies primarily on the high-threshold recollection process, then the rec ognition zROCs should have a shallower slope for source-correct than source-incorrect items and the refined source zROC must be u-shaped (see Figure ,3, Panel 1). If familiarity drives source 3 The BBG model is similar, but not identical, to the proposal that participants make random source guesses for any item they fail to recog nize (Hautus et al, 2008;Slotnick & Dodson, 2005). One critical differ ence is that the point where the bounded distributions converge is not determined by a participant's criterion for making an "old" response, so in the BBG model, it is possible for "new" responses to have above chance source discrimination if the recognition criterion is sufficiently conserva tive (as observed by Stams, Hicks, Brown, & Martin, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the model could predict that if one selects out targets that received a high confidence "new" response, then the Source A items should be consistently attributed to Source B, and vice versa (Hautus et al, 2008). Of course, this pattern is not observed in empirical data.…”
Section: The Bounded Bivariate Gaussian (Bbg) Modelmentioning
confidence: 97%
“…Indeed, ROC analysis is widely used to differentiate between competing theories of recognition memory in the experimental psychology literature (e.g., Hautus, Macmillan, & Rotello, 2008;Heathcote, 2003;Mickes, Johnson, & Wixted, 2010). However, as Clark et al (2011) observed, theoretical accounts of eyewitness memory are in short supply.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent UV SDT extensions acknowledge the importance of encoding-related factors (Hautus, Macmillan, & Rotello, 2008). Additionally, assessments of the competing views of recollection have often focused on either neuroimaging or cognitive modeling (see Malmberg, 2008 for review).…”
mentioning
confidence: 99%